Effect of Magnetic Stirring, Grain Modification and Refinement on the Solidification Structure of an a356 Aluminum Alloy - Bustos-Castillo, O; Sanchez-Villa, C; Allende-Seco, R; Leiva-Illanes, R (Universidade Federal do Rio de Janeiro, 2021)
The effect of the application of forced convection during the continuous solidification of Al-Si alloys has been presented in this work. The investigation has been made on the hypothesis that as an alloy solidifies under the action of a rotating magnetic field, a nondendritic casting structure would be obtained. The Al-Si alloy has been studied in its three different states (original, modified, and modified with a grain refiner), using a magnetic stirring equipment with permanent magnets, a device that has allowed the study of the effect of the rotational speed (degree of stirring) on the micro-and macro-solidification structure, as well as on the material’s mechanical properties. With the purpose of validating the hypothesis, different analyses and tests have been carried out, such as thermal analysis of the solidification process, micro-and macrostructural anal-ysis, and hardness measurements for the different process conditions studied. The results have shown that magnetic stirring affects the cooling curves, expanding the solidification range. A microstructural evolution of the alloys has also been observed, from a 100% dendritic structure to a mature rosette type structure, in addition to a notable decreasing of grain size, which results in the improvement of the material’s mechanical behavior. © 2021, Universidade Federal do Rio de Janeiro. All rights reserved.
Keywords: Al-Si; Forced convection; Grain Refinement; Solidification